1998
DOI: 10.1182/blood.v92.1.252.413k08_252_258
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 Is an Autocrine/Paracrine Viability Factor for Cutaneous T-Cell Lymphoma Cells

Abstract: In this study we investigated the role of interleukin-15 (IL-15) in the immunobiology of cutaneous T-cell lymphoma (CTCL) cells. Using cell culture techniques, reverse transcriptase-polymerase chain reaction (RT-PCR), and immunhistochemistry we found that IL-15, like IL-7, is a growth factor for the Sézary cell line SeAx and that both cytokines prolonged the survival of malignant T cells directly isolated from Sézary syndrome (SS) patients. Both IL-15 and IL-7 were more potent than IL-2. IL-4 and IL-9, whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(83 citation statements)
references
References 29 publications
5
75
1
2
Order By: Relevance
“…We describe here the establishment of an animal model for MF. The cell line MyLa, used in our study, is derived from a tumor biopsy of an MF patient and grows cytokine independent under tissue culture conditions (9). Subcutaneous transplantation of MyLa cells generated large subcutaneous tumors in immune deficient nu/nu mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We describe here the establishment of an animal model for MF. The cell line MyLa, used in our study, is derived from a tumor biopsy of an MF patient and grows cytokine independent under tissue culture conditions (9). Subcutaneous transplantation of MyLa cells generated large subcutaneous tumors in immune deficient nu/nu mice.…”
Section: Discussionmentioning
confidence: 99%
“…The lymphocytes were purified from spleen or lymph nodes. Cells were expanded in tissue culture for 3 weeks without the addition of cytokines, because MyLa cells are able to grow cytokine independently (9). Cells derived from blood, lymph node, and spleen expressed the human CD4 receptor, grew independently of interleukins and were thereby identified as MyLa cells (data not shown).…”
Section: Pcr Analysis Of the Human Cd4 Receptor (Data Not Shown) A Cmentioning
confidence: 99%
“…IL-15 [41] und IL-7 [28] sind potente Wachstumsfaktoren für CTCL-Zelllinien und verlängern in vitro die Überlebenszeit von CTCL-Zellen von Patienten mit Sézary-Syndrom. IL-15 wird in Keratinozyten der Basalschicht und dendritischen Hautzellen exprimiert [29], jedoch ebenso von neoplastischen Lymphozyten [30], was zu einer autokrinen Schleife der Zellstimulation führt. Neue Ansätze zur Therapie können sich aus der Modulation von Homing-Rezeptoren ergeben.…”
Section: Infektiöse Faktorenunclassified
“…IL-2, IL-7, IL-9, IL-15, IL-21). [37][38][39][40] Consequently, blood eosinophil counts and IgE-t are frequently increased in SS and advanced MF. Tancr ede-Bohin et al 41 reported that blood eosinophilia (>700 eosinophils/lL) was present in 10 of 13 (77%) patients with SS.…”
Section: Discussionmentioning
confidence: 99%